ANALISIS KELAYAKAN FINANSIAL USAHA AGROINDUSTRI KUE KUE BAWANG DI KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU (Studi Kasus Usaha Kue Bawang Bina Karya) - Prisma Roviyanti; Yusmini '; Susy Edwina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are to analyse the financial feasibility of Bina Karya’s onion stick agroindustry business and to know sensitivity rate of Bina Karya’s onion stick agroindustry business in Rengat District Indragiri Hulu Regency. This research used case studymethod. The financial feasibility analysis of onion stick agroindustry business used investment criterias, such as: Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit-Cost Ratio (Net B/C). The result showed that onion stick agroindustry business feasible to developed based on its investment criterias, which showed that NPV was Rp. 482.206.098 (positive), IRR value was 53% (IRR more than DF 12%), and Net B/C value was 3,29 (Net B/C more than 1). The result of sensitivity analysis by the raw material price increase, such as the flour price increase (wheat and tapioca flour) at the rate of 7% impact to NPV is Rp. 466.222.711 (positive) and the onion and garlic price increase (garlic at the rate of 112% and onion at the rate of 110%) impact to NPV is Rp. 381.852.159(positive). Other result of sensitivity analysis by decrease ofproduction scale more than 23% showed that this agroindustry business not feasible to develop because NPV is negative value, IRR smaller than DF 12 %, and NetB/C value smaller than 1. Keywords: Agroindustry, Financially Analysis,Sensitivity Analysis